43.0k views
0 votes
3x + 2(4 +6x) = 113 can someone please explain

2 Answers

7 votes
Simplifying
3x + 2(4 + 6x) = 113
3x + (4 * 2 + 6x * 2) = 113
3x + (8 + 12x) = 113

Reorder the terms:
8 + 3x + 12x = 113

Combine like terms: 3x + 12x = 15x
8 + 15x = 113

Solving
8 + 15x = 113

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-8' to each side of the equation.
8 + -8 + 15x = 113 + -8

Combine like terms: 8 + -8 = 0
0 + 15x = 113 + -8
15x = 113 + -8

Combine like terms: 113 + -8 = 105
15x = 105

Divide each side by '15'.
x = 7

Simplifying
x = 7
User DannyPhantom
by
6.3k points
3 votes
Distribute the 2 to the numbers in the parenthesis. This gives you 3x+8+12x = 113. Add 3x and 12x to get 15x. Subtract 8 from both sides. This leaves u with 15x = 105. Then isolate variable so divide by 15 to both sides. x=7
User Wael Dalloul
by
6.2k points